Tingkat Kecemasan pada Lansia terhadap Hipertensi di Kelurahan Sidodadi Kecamatan Wonomulyo - Rani, Rani; Darmiati, Darmiati (Mando Care Jurnal, 2023)
The elderly are a group that is very vulnerable to various health problems, both physical and psychosocial, which are vulnerable and ofter occur in the elderly. Therefore, it is very important to know the levels of problems experienced by the elderly, both health problems and the level of alertness and anxiety of the elderly towards the health problems they experience. One of the mots common health problems in the elderly is hypertension, 1 billion elderly people in the world 1 or 4 elderly suffering from hypertension will increase to 1.6 billion in 2025. There are several alderly people in Polewali Mandar Regency, especially the elderly, Wonomulyo Distict, Sidodadi Village. Village data and the results from the survey we obtained of the elderly in the Sidodadi village most of the elderly there have hypertension and not a few of them are taking herbal medicines which are believed to reduce hypertension levels, there are also elderly who feel anxious due to hypertension that is suffered continuously for a long time. Anxiety is one of the mental health problems that most often arises, plus if the elderly have a history of disease, one of which is hypertension. The research method that we applied in thi study used a survey method and a quantitative approach, observing the results of the data that had been submitted in the questionnaire.